Opportunities in optical and electrical single-cell technologies to study microbial ecosystems - Mermans, Fabian; Mattelin, Valérie; Van den Eeckhoudt, Ruben; García-Timermans, Cristina; Van Landuyt, Josefien; Guo, Yuting; Taurino, Irene; Tavernier, Filip; Kraft, Michael; Khan, Hira; Boon, Nico (Frontiers in Microbiology, 2023)
New techniques are revolutionizing single-cell research, allowing us to study microbes at unprecedented scales and in unparalleled depth. This review highlights the state-of-the-art technologies in single-cell analysis in microbial ecology applications, with particular attention to both optical tools i.e. specialized use of flow cytometry and Raman spectroscopy and emerging electrical techniques. The objectives of this review include showcasing the diversity of single-cell optical approaches for studying microbiological phenomena, highlighting successful applications in understanding microbial systems, discussing emerging techniques, and encouraging the combination of established and novel approaches to address research questions. The review aims to answer key questions such as how singlecell approaches have advanced our understanding of individual and interacting cells, how they have been used to study uncultured microbes, which new analysis tools will become widespread, and how they contribute to our knowledge of ecological interactions.